A new student-led digital drawing course: an initiative to bridge patient health literacy through medical illustrations. (3rd July 2022) - Kellner, Rebecca L.; Agathis, Alexandra Z.; Moon, James K.; Garfinkle, Suzanne; Appel, Jacob; Coakley, Brian A.
Abstract: Many physicians believe illustrations can be helpful in patient encounters, but fail to create such drawings due to a perceived lack of artistic ability. Digital drawing platforms, however, have the ability to compensate for the lack of artistic skills. Our study sought to evaluate how digital drawing instruction would impact the likelihood of medical students to utilise illustrations in future patient encounters. 'Draw Your Way Through Medicine' was an elective course, offered at the Icahn School of Medicine at Mount Sinai in 2020. The course instructed students how to create digital drawings using Procreate and how to depict specific surgical procedures. Students completed pre-and post-course surveys, which were analysed using paired t-tests. Thirty-six students enrolled in the course, of which 27 completed the pre-course survey and 21 completed both pre-and post-course surveys. Students' comfort level with drawing improved somewhat (3.0 to 3.5, p  = .08), while their comfort level with creating medical illustrations improved significantly (2.2 to 3.7, p  < .01). Qualitative responses echoed the enthusiasm for implementing digital drawing as a clinical communication tool. A digital drawing course showed considerable value in improving medical students' confidence in generating medical illustrations, making this form of visual communication a potentially valuable tool in patient care.